Computer classroom at home (Southbank, Vic. : Thomson Nelson, 2003)
Features interactive lessons with colourful characters who introduce topics in spelling, reading and spelling, and act as study partners when children need assistance.
Spelling -- Reading -- Maths.
"Triple pack"--Box cover.
"Grade 3/4"--Cover.
For ages 7-10.
System requirements: Windows 98/NT4/2000/ME/XP, Mac System 8.6 to 9.9, Mac System OS X.
Keywords: English language -- Orthography and spelling -- Computer-assisted instruction; Reading -- Computer-assisted instruction; Mathematics -- Computer-assisted instruction